Revitalization of Coffee Husk Waste into Visual Art Works Based on the Local Identity of Wonosobo - Doni muhammad farid; Muhammad Rivakhul Huda; Ahmad Dwi Satriyo; Fauza Chairul Athfal; Eni Candra Nurhayati (Center for Intellectual Property and Technology Innovation, Universitas Sains Al-Qur'an, 2026)
The growing volume of coffee husk waste worldwide, particularly on the slopes of Mount Sindoro–Sumbing in Wonosobo Regency, presents a major environmental challenge as this agricultural by-product remains underutilized. This study aims to analyze the influence of green product attributes and environmental awareness on consumer purchase intention toward waste-based artwork, specifically through the revitalization of coffee husks into sustainable visual art. Adopting a practice-based approach, the method encompasses conceptual planning, material cleaning and drying, manual crushing to achieve varied textures, and selective application onto canvas using an adhesive medium. The results demonstrate that coffee husk waste can be effectively transformed into a visually compelling human portrait, showcasing clear forms, visual depth, and rich tonal variations without relying on synthetic pigments. Ultimately, this approach impacts the field by establishing a reproducible model for eco-friendly art production that challenges conventional perceptions of waste. By successfully bridging environmental consciousness and creative expression, the final product communicates powerful messages of sustainability while simultaneously opening new green innovation pathways to stimulate the regional creative economy.